Biomaterial Applications for Stem Cell-Derived Exosome Therapy - Hur, Grace; Kim, Ian; Yazdy, Atta (The Meducator, 2025)
Stem cell-derived exosomes (SC-Exos) continue to emerge as a prominent and versatile cell-free therapy for promoting tissue regeneration and bioactive signalling. However, clinical translation is limited by challenges in targeted delivery, stability, and short circulation lifespans. To address these barriers, biomaterials that can protect exosomal integrity and allow for controlled release have been increasingly explored as effective delivery platforms. Understanding how such biomaterials can influence the outcomes of exosomal therapy is critical for advancing clinical applications and optimizing therapeutic potential.